A negative bias in decoding positive social cues characterizes emotion processing in patients with symptom-remitted Borderline Personality Disorder - Kleindienst, Nikolaus; Hauschild, Sophie; Bertsch, Katja; Lis, Stefanie (Borderline Personality Disorder and Emotion Dysregulation, 2019)
Impairments in the domain of interpersonal functioning such as the feeling of loneliness and fear of abandonment have been associated with a negative bias during processing of social cues in Borderline Personality Disorder (BPD). Since these symptoms show low rates of remission, high rates of recurrence and are relatively resistant to treatment, in the present study we investigated whether a negative bias during social cognitive processing exists in BPD even after symptomatic remission. We focused on facial emotion recognition since it is one of the basal social-cognitive processes required for successful social interactions and building relationships.